Impact of Timing of Concurrent Chemoradiation for Newly Diagnosed Glioblastoma: A Critical Review of Current Evidence. (August 2015) - Han, Seunggu J.; Englot, Dario J.; Birk, Harjus; Molinaro, Annette M.; Chang, Susan M.; Clarke, Jennifer L.; Prados, Michael D.; Taylor, Jennie W.; Berger, Mitchel S.; Butowski, Nicholas A.
Abstract : ABBREVIATIONS: EORTC/NCIC, European Organisation for Research and Treatment of Cancer/National Cancer Institute of Canada GBM, glioblastoma OS, overall survival PFS, progression-free survival SEER, Surveillance, Epidemiology, and End Results TMZ, temozolomide